A cadaveric study of deep branch of radial nerve at arcade of Frohse - R Sivachidambaram; T H Dilipkumar; A Stellamary (Wolters Kluwer Medknow Publications, 2022)
Background: The arcade of Frohse (AF) is the most common site for compression of the deep branch of the radial nerve (DBRN). During the surgical fixation of proximal radial shaft fracture, there is a chance of accidental injury to DBRN near the arcade. The objective of the study was to describe the nature of AF, to provide the superficial surgical landmark for DBRN at AF, and to indicate the appropriate position of the forearm for the surgical approach in fracture proximal radial shaft surgery. Methodology: The present study was done on 50 upper extremities preserved in 10% formalin. The studied parameters were morphology of AF, forearm length, the distance between the lateral epicondyle and the DBRN at AF, arcade ratio and the distance of DBRN at AF to the biceps tendon in pronated and supinated forearm. Results: In 50 upper extremities, the AF was tendinous in 27 limbs (54%), musculotendinous in 19 limbs (38%), and membranous in 4 limbs (8%). The mean forearm length was 234.43 mm. The mean distance from the DBRN to the lateral epicondyle was 48.98 mm. The mean arcade ratio was 0.208 mm. At AF, the mean distance from DBRN to the biceps tendon in pronation and supination was 12.72 mm and 18.98 mm, respectively. Conclusion: The most common type of AF is tendinous type. The mean arcade ratio derived from our study was 0.208. It is suggested that the terminal supination of the forearm is the appropriate position for surgical reduction and fixation of proximal radial shaft fracture through the ventral (Henry's) approach.